Study of Lateral Load Influence on Behaviour of Negative Skin Friction on Circular and Square Piles - Omar Shawky; Ayman I. Altahrany; Mahmoud Elmeligy (Civil Engineering Journal, 2022)
Negative skin friction developed on the pile surface causes many problems when piles are built in fully saturated clay. In this work, a study of NSF on a square cross-section pile corresponding to the circular pile circumference was developed. The pile was modeled as a concrete element, embedded and fully contacted with fully saturated soft clay. The clay layer is supported on a sand layer as a sub-base using ABAQUS software, and the NSF was developed on piles due to the consolidation of the clay over a 5-year period. A square pile has been found to provide lower NSF values than a round pile. Then, for the first investigation, both piles were loaded with lateral loads at the top to investigate the effect of the horizontal load on the NSF values, as there is no literature or study done on this point. The results emphasized that lateral loads reduce the NSF developed on piles. A parametric study was performed to investigate the parameters affecting the NSF values induced on piles, such as soil permeability, ballast, and lateral load values. It was concluded that square piles provide better NSF values than round piles for both single piles and pile groups. Doi: 10.28991/CEJ-2022-08-10-08 Full Text: PDF